Tensions From Within: Perspective On State Fragility and Internal Security Challenges in Nigeria (Integral Research, 2025)
The people's security and welfare are the Nigerian government's primary purposes. Unfortunately, the Nigerian state has often demonstrated an inability to perform these critical functions over the years. This study examined the link between the fragility of the Nigerian state and the expanding internal security challenges across the country. Data for the study were sourced from documentary evidence, like scholarly literature, newspapers, official documents of relevant organisations, and agencies. Utilising the analytical assumptions of the theory of state fragility, the study found that the fragility of the Nigerian state in terms of authority, capacity, and legitimacy contributes to the pervasive incidence of internal insecurities in the country.
Keywords: Authority, Challenges, Internal Security, Nigeria, Security, State Capacity, State Fragility, and Threat.